FAMILY CHLOROPIDAE - Riccardi, Paula Raile (Zootaxa, 2016)
The Chloropidae representatives from Colombia are poorly known, and are represented by one Shiphonellopsinae genus, five Chloropinae genera and 19 Oscinellinae genera, in a total of 46 described species.